Impact of Health Education on Knowledge About Polycystic Ovarian Syndrome (PCOS) Among Nursing Students in Bhubaneswar, Odisha - Kar, Chanchala; Puhan, Kabita; Dalai, Bishnupriya; Sahoo, Sushrita; Mohapatra, Nirupama; Mohapatro, Puspanjali; Tripathy, Rojy (Journal of Neonatal Surgery, 2025)
Polycystic Ovary Syndrome (PCOS) is a common hormonal disorder among women of reproductive age, characterized by irregular menstruation, elevated androgen levels, and often ovarian cysts, which can lead to serious reproductive and metabolic complications such as infertility. This study aimed to evaluate the effectiveness of a structured teaching programme in enhancing knowledge about PCOS among adult girls at Hi-Tech School and College of Nursing, Bhubaneswar. The study employed a descriptive survey method and a pre-test post-test research design. A total of 50 adult girls were selected as the sample. Data was collected using a structured questionnaire administered before and after the educational intervention, which included an informative booklet on PCOS. The pre-test results revealed that only 44% of participants had average knowledge, with a mean score of 13.2 (SD ±5.6). After the structured teaching programme, the post-test mean score significantly increased to 23.34 (SD ±4.62), translating to a mean percentage of 77.8% and a knowledge gain of 33.8%. The decrease in standard deviation indicated more consistent knowledge levels among participants post-intervention. A t-value of 9.88 with 49 degrees of freedom and a p-value of 0.000 demonstrated that the improvement in knowledge was statistically highly significant. These findings confirm the effectiveness of structured teaching in increasing awareness and understanding of PCOS. The study suggests that health education interventions can play a crucial role in addressing knowledge gaps among young women, potentially leading to better health outcomes. It also recommends conducting further studies with larger samples and diversified methods such as interviews to enhance the depth and generalizability of the findings. In conclusion, the study highlights health education as an essential strategy in empowering young women with the knowledge to manage and prevent complications related to PCOS